The Influence of Promotion and Knowledge for the Completeness of Basic Immunization in Infants - Marniati Marniati; Susy Sriwahyuni; Nur Nadiah (Universitas Teuku Umar, 2020)
Background departs of research from immunization coverage problems The background of the study departs from the problem of immunization coverage which is still very low, namely the percentage of immunization coverage in Tangkeh Health Center in 2018 Hb0 15.7%, BCG 36.3%, Polio 1 63.7%, DPT 1 50%, DPT 2 40.2 %, Polio 3 38.2%, DPT 3 22.5%, Polio 4 32.4%,Measles 25.5% of the standard service of at least 99%. This study aims to look at the effect of promotion and knowledge for completeness of basic infant immunization in the working area of Tangkeh Health Center in West Aceh District. Method of reseach wasquantitative method with cast control design. Population amounted to 74, Samples were taken accidentally sampling which is 30 baby mothers. The software used to analyze was SPSS 22, the bivariate analysis with T-test independent. The results of bivariate analysis was promotion (P value 0.003 <α; 0.05) and knowledge (P value 0.012 <α; 0.05), which means was the promotion and knowledge have an influence on completeness of basic immunization in infants with a poin of promotion higher average posttest (9.77) better than pretest (5.50) and with poin of knowledge higher average posttest (8.75) better than pretest (6.35).The conclusion of the study was the promotion and knowledge influences the completeness of basic immunization in infants.